(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Concrete is one of the most widely used construction materials, but its production contributes to significant environmental concerns due to the high consumption of natural resources and the generation of large amounts of waste. In recent years, efforts have been made to incorporate industrial by-products, such as fly ash and slag, into concrete to enhance its sustainability and performance. This research paper investigates the combined effect of incinerated biomedical waste ash (IBWA) and pond ash (PA) as supplementary cementitious materials on the properties of concrete. The study involves an experimental investigation conducted to evaluate the fresh and hardened properties of concrete incorporating different proportions of IBWA and PA. Concrete mixes with varying replacement levels of cement by IBWA and PA are prepared and their workability, compressive strength, split tensile strength and flexural strength are examined. The results reveal that the compressive strength, split tensile strength and flexural strength of the concrete specimens are found to increase up to a certain replacement level and then gradually decrease. The improvements in concrete properties can be attributed to the pozzolanic and filler effects of IBWA and PA, which contribute to the formation of additional hydration products and denser microstructures. This research provides valuable insights into the potential utilization of incinerated biomedical waste ash and pond ash as sustainable alternatives to conventional cement in concrete production. The findings highlight the feasibility of reducing the environmental impact associated with the disposal of wastes while simultaneously enhancing the performance of concrete. The outcomes of this study can be instrumental in promoting the adoption of environmentally friendly practices in the construction industry and facilitating the development of guidelines for incorporating IBWA and PA in concrete mix designs.